(untitled) (Research, Society and Development, 2022)
The aim of this study was to present a comprehensive evaluation of the chemical composition, anti-inflammatory and antioxidant activities of the pulp and seeds of Eugenia candolleana fruits collected at two stages of maturation. The results showed that fruits are a good source of vitamins and minerals such as thiamine and riboflavin, iron, phosphorus, magnesium, manganese, potassium and zinc, besides high amounts of protein and dietary fiber. The fruits showed a higher proportion of unsaturated fatty acids, with a predominance of linoleic acid in all samples. The seeds presented a significantly higher content of phenolic and tannins than pulp, however, anthocyanins were found exclusively in the pulp and skin of the fruits. Maturation affected the composition of phenolics where the mature stage presented significantly fewer phenolic compounds. Quercetin, pyrogallol and gallic acid were the main compounds identified in the pulp and seeds. Both pulp and seeds presented potential antioxidant and anti-inflammatory activities, however, the seeds have significantly higher activity. The seed extracts significantly reduced the production of nitric oxide and the cytokines IL-6 and TNF-α in macrophages, highlighting a potential anti-inflammatory activity. The fruits can be included in diets as a strategy to improve the diversity of food supply, in addition, the seed flour can be used as a potential food supplement, besides valuing agro-industrial by-products.